Systemic inflammatory markers and outcome in patients with locally advanced adenocarcinoma of the oesophagus and gastro-oesophageal junction. Issue 4 (10th January 2017) - Jagadesham, V P; Lagarde, S M; Immanuel, A; Griffin, S M
Abstract: Background: Raised levels of systemic inflammatory markers are associated with poor survival in patients with cancer. The aim of this study was to assess the prognostic value of markers of systemic inflammation in patients with adenocarcinoma of the oesophagus or gastro-oesophageal junction. Methods: Data from a consecutive series of patients undergoing transthoracic oesophagectomy following neoadjuvant therapy at a single centre were analysed. Fibrinogen, albumin, C-reactive protein, leucocyte differential and platelet counts were measured before surgery. The upper quartile (75th percentile) was used as a cut-off for dichotomization. Multivariable regression analysis was performed to identify independent prognostic factors. Results: A series of 199 patients underwent transthoracic oesophagectomy following neoadjuvant therapy. Univariable analysis indicated that reduced median survival was associated with a raised platelet : lymphocyte ratio (158 or above; 25.6 versus 44·4 months for patients with a normal ratio, P = 0·038) and increased fibrinogen levels (4·9 g/l or above; 22·8 versus 59·9 months for those with a normal level, P = 0·005). On multivariable analysis a combination of one or more markers of systemic inflammation was associated with poorer overall survival (hazard ratio 2·12, 95 per cent c.i. 1·20 to 3·74; P = 0·010). Conclusion: Preoperative markers of systemic inflammation predict poor outcome in patients undergoing curative treatment for locally advanced oesophageal and gastro-oesophageal adenocarcinoma. Abstract : Could help in treatment stratification